Post‐transcriptional regulation of C‐C motif chemokine ligand 2 expression by ribosomal protein L22 during LPS‐mediated inflammation. (25th May 2020) - Das, Anindhya Sundar; Basu, Anandita; Kumar, Ravi; Borah, Pallab Kumar; Bakshi, Subhojit; Sharma, Manoj; Duary, Raj Kumar; Ray, Partho Sarothi; Mukhopadhyay, Rupak
Abstract: Monocyte infiltration to the site of pathogenic invasion is critical for inflammatory response and host defence. However, this process demands precise regulation as uncontrolled migration of monocytes to the site delays resolution of inflammation and ultimately promotes chronic inflammation. C‐C motif chemokine ligand 2 (CCL2) plays a key role in monocyte migration, and hence, its expression should be tightly regulated. Here, we report a post‐transcriptional regulation of CCL2 involving the large ribosomal subunit protein L22 (RPL22) in LPS‐activated, differentiated THP‐1 cells. Early events following LPS treatment include transcriptional upregulation of RPL22 and its nuclear accumulation. The protein binds to the first 20 nt sequence of the 5′UTR of ccl2 mRNA. Simultaneous nuclear translocation of up‐frameshift‐1 protein and its interaction with RPL22 results in cytoplasmic degradation of the ccl2 mRNA at a later stage. Removal of RPL22 from cells results in increased expression of CCL2 in response to LPS causing disproportionate migration of monocytes. We propose that post‐transcriptional regulation of CCL2 by RPL22 fine‐tunes monocyte infiltration during a pathogenic insult and maintains homeostasis of the immune response critical to resolution of inflammation. Databases: Microarray data are available in NCBI GEO database (Accession No GSE126525 ). Abstract : LPS induces early transcriptional upregulation of both C‐C chemokine ligand 2 (CCL2) and ribosomal protein L22 (RPL22) in macrophages. RPL22 is translocated into the nucleus and interacts with the ccl2 5′UTR sequence. Up‐frameshift‐1 protein is also translocated into nucleus and interacts with RPL22, and the RNP complex is exported to cytoplasm. The ccl2 mRNA is degraded subsequently, emphasizing the role of ribosomal protein in maintaining the homeostasis of monocyte migration.